The Holonomy Decomposition of some Circular Semi-Flower Automata - Singh, Shubh N.; Krishna, Kanduru V. (Acta Cybernetica, 2016)
Using holonomy decomposition, the absence of certain types of cycles in automata has been characterized. In the direction of studying the structure of automata with cycles, this paper focuses on a special class of semi-flower automata and establish the holonomy decomposition of certain circular semiflower automata. In particular, we show that the transformation monoid of a circular semi-flower automaton with at most two bpis divides a wreath produt of cyclic transformation groups with adjoined constant functions.